A Review on Comprehensive Development of Conceptual Framework for Scoring Tool of Professionalism Assessment Among Medical Undergraduates in Malaysia - Nik Ahmad Shaiffudin, Nik Him; Azizul Fadzli, Wan Jusoh@Ab Rahim; Norhasiza, Mat Jusoh; Nordin, Simbak (2018)
Assessment of professionalism is a global issue in undergraduate medical training. The issues is about addresing its practice and valid assessment and not merely doctor-patient relationship. An attempt translate general professional behaviours as competencies to specific observable behaviours in clinical practice is the new concepts to develope the new scoring tools in this proposal for a comprehensive research framework. The aim is to measure professional behaviour from widely practiced, qualitative to a quantitative assessment of undergratuate medical student. As an outcome, the framework will explore the the current practice of observable professionalism and behaviour highlighting its strenghts,weakness and gaps in understanding the comprehensive approach of professionalism assessment. Keywords – professionalism, medical undergraduates, work-based assessment and scoring tools